Noctiluca scintillans: Dynamics, Size Measurements and Relationships With Small Soft-Bodied Plankton in the Belgian Part of the North Sea - Ollevier, Anouk; Mortelmans, Jonas; Aubert, Anaïs; Deneudt, Klaas; Vandegehuchte, Michiel B. (Frontiers in Marine Science, 2021)
Climate driven changes and anthropogenic pressures on the marine environment have been shown to favor the increase in certain potentially harmful species. Among them, Noctiluca scintillans, a common dinoflagellate, often blooms during warm summers and is known to affect plankton communities. In this study, we assessed the dynamics in abundance and cell size of N. scintillans as well as the relationship between N. scintillans and small soft-bodied zooplankton in the Belgian Part of the North Sea, since negative correlations between these plankton groups have been previously reported for nearby regions. This study is the first to present consistently counted N. scintillans cell numbers and measured cell lengths, through the analysis of ZooScan images from samples taken monthly at stations throughout the coastal zone of the Belgian Part of the North Sea. The results show that N. scintillans demonstrated clear seasonal dynamics with both high densities and large cell sizes in spring/summer (May-July). The occurrence of N. scintillans in the analyzed plankton samples and the abundance of N. scintillans at the observed peak intensities nearly tripled over a period of five years. A zero-inflated model showed a correlation of N. scintillans abundance with temperature as well as with phosphate concentrations, suggesting that anthropogenic influences such as climate change and riverine nutrient inputs could affect the temporal dynamics of the species. The results, on the other hand, did not show any negative impact of N. scintillans on the soft-bodied plankton community.